Faces of joblessness in Australia An anatomy of employment barriers using household data - Immervoll, Herwig (OECD Social, Employment and Migration Working Papers, 2019)
Although Australia's labour market escaped the dramatic negative impact of the global financial economic crisis seen in other OECD countries, a substantial share of working-age Australians either did were not working or worked only to a limited extent as the global recovery gathered pace between 2013 and 2014. The paper extends a method proposed by Fernandez et al. (2016) to measure and visualise employment barriers of individuals with no or weak labour-market attachment, using household micro-data. The most common employment obstacles in Australia are limited work experience, low skills and poor health. A notable finding is that almost one third of jobless or low-intensity workers face three or more simultaneous barriers, highlighting the limits of policy approaches that focus on subsets of these employment obstacles in isolation. A statistical clustering approach points to seven distinct groups, each characterized by unique profiles of employment barriers that call for different configurations of activation and employment-support policies